A randomized comparison of terbinafine vs. itraconazole for the treatment of tinea capitis- A prospective comparative study in health care centers of Southern Punjab: Treatment of tinea capitis - Siddique, Ambreen; Fiaz-ud-Din Ahmad; Uzair Ahmed Qureshi (Journal of Pakistan Association of Dermatologists, 2023)
Background: Tinea capitis is considered as one of the most frequent dermatophyte infections of the scalp in children, predominantly caused by Trichophyton or Microsporum species. On account of host predilection and habitation dermatophyte are codify as anthropophilic, geophilic and zoophilic. The etiological agent of tinea capitis usually falls in first and last categories. In Pakistan Trichophyton Violaceum is the frequent etiological agent responsible for 69.4 percent of infections, followed by T. tonsurans 16 percent, T. verrucosum 10 percent, M. audouinii 2.2 percent. Ringworm of scalp frequently noticed among 6-year-old minors and before puberty, distinguished by grey path on scalp, black dot pattern, hair loss, inflammatory kerion, favus (less common), pustules and generalized scaling. Diagnostic test for tinea capitis comprises clinical presentation, 10-30% KOH direct microscopy, culture media and wood lamp examination (useful in certain ectothrix infections). Treatment of dermatophyte infection necessitates primarily oral and/or topical formulation of azoles or allylamine, particularly itraconazole and Terbinafine. Terbinafine an allylamine antifungal, was FDA approved in 1996 but has an implication for the treatment of local non-systemic fungal infection. Itraconazole was approved in 1992 to treat superficial fungal infections. For superficial fungal infection such as tinea capitis, oral anti-fungal are the principal treatment provided. Terbinafine is the drug of choice for the treatment of tinea capitis. Oral antifungal drugs presumably correlated with severe hepatotoxity, rare serious skin events such as Steven-Johnson syndrome and possible drug-drug interaction due to metabolism through cytochrome P-450 system. Objective: Objective of this study was to evaluate the therapeutic efficacy of terbinafine in comparison with itraconazole in treatment of tinea capitis. It is pertinent to mention that tinea capitis is a pronounced disease of Southern Punjab with specific prevalence in children of Bahawalpur and surroundings in prepubertal stage, which merits a definite consideration owing to inherent implications and limitations of the disease. Method: The Prospective comparative study conducted at health care centers of southern Punjab. It comprised 100 children aged 5-16 years, with clinically and mycologically confirmed tinea capitis by 10-30% KOH microscopy and by Sabouraud agar. The children randomized to 8 weeks’ treatment with terbinafine or 8 weeks with itraconazole. Evaluation criteria resorted to constitute inspection of random sample of patient at 0, 2,4 and 8-week interval. Efficacy analysis based upon pooled data and photographic documentation. Outcome determined by absence of clinical signs. Safety assessment included monitoring of the frequency and severity of adverse events (AEs). Hepatic safety of itraconazole (Azole group) determined by LFTs after 4-week treatment. Data analysis conducted with SPSS and graph pads. Result presented in tabular and pictorial form. Result: There were 80 cases in both group A (Terbinafine) and group B (Itraconazole), with no tremendous contrast as far as average age, weight, pre-treatment, total sign and symptom score and number of sores. Fix was seen remarkably superior in bunch B where 70 (87.5%) cases were relieved when contrasted with bunch A where 56 (70%) cases were restored. The tolerability was likewise essentially better in bunch B, where 62 (77.5%) sufferers have either excellent or great reaction to medicate resilience as compare to bunch A where it is noticed in 42 (52.5%) sufferers. Conclusion: Itraconazole manifest noteworthy benefits with regards to cure rate, time requires for rehabilitation and acceptability which appeares differently in relation to terbinafine.